An Examination of Preservice Teachers’ 21st Century Learner and Teacher Skills Based on Different Variables - Bakir, Siddik (Asian Journal of Education and Training, 2019)
This study examined the levels of preservice teachers’ 21st century learner and teacher skills and the relationship between these two types of skills in terms of different variables. This study was a correlational survey. The data were collected using three instruments: the “21st Century Learner Skills Use Scale” and the “21st Century Teacher Skills Use Scale” developed by Orhan (2016) and a “Personal Information Form” prepared by the researcher. The population of the study consisted of preservice teachers studying at a state university located in the Eastern Anatolia Region of Turkey in the spring semester of the academic year of 2018–2019. The sample consisted of 445 preservice teachers determined by using the simple random sampling method from among the departments determined based on the cluster sampling method. Based on the results of the study, the use of the learner and teacher skills of the preservice teachers differed significantly depending on different variables such as gender, grade level and department, and there was a positive significant correlation between their uses of learner and teacher skills. It is hoped that the study will contribute to preservice teachers and the literature in terms of teacher competencies and education.